Mother-son enmeshment and its implications for the emancipation-individuation process: a case study study - Gijana, Eucliffe Wycliffe Mphumzi (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
This case study reports on a patient who was undergoing psychotherapy for an Adjustment Disorder with Mixed Emotional Features. The aim of the study had two aspects. First the study sought to establish to what degree was enmeshment between the patient and his mother responsible for his maladaptive behaviour. The second aspect was to establish the extent to which the patient responded to psychotherapy. The patient was a 20 year old male university student. He was experiencing a number of problems including difficulty in interpersonal relations, deteriorating academic performance, depression, anxiety and uncertainty about career choice and about the future. The history revealed that the patient had very close and enmeshed relations with his mother. The mother was a very domineering person and had great influence on her son. On the other hand his father was weak and emotionally unavailable. The patient had never been away from home until after he graduated from High School and decided to join the army. It was then his problem began to manifest. He left the army and registered at university. However, the problems continued and even increased in intensity. It was hypothesized that as a result of enmeshment with his mother and the fact that his mother was a domineering personality, he never had the opportunity to learn social skills that would have enabled him to emancipate himself from his mother . Thus when he moved out of home to be on his own, first in the army and later at university, he could not cope. He lost self-confidence, became passive, indecisive and dependent. Psychotherapy was successful in helping him gain insight into the genesis of his problem. This insight resulted in the patient's efforts towards individuation.
Keywords: Uncatalogued